Interactive Learning Media Development Based on Game-Based Learning and Ethnomathematics Using Lumi - Rani Puja Savitri; Ira Kurniawati; Dyah Ratri Aryuna (Jurnal Karya Pendidikan Matematika, 2026)
This research focuses on development of interactive learning media using the Lumi Education platform based on game-based learning and ethnomathematics on the topic of straight line equations to improve students’ learning interest. The study adopted a research and development approach based on the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The developed media integrates game-based learning through a game map feature and ethnomathematics by incorporating cultural contexts into learning activities. The study was conducted with eighth-grade students of SMP Negeri 27 Surakarta. Data were obtained through expert validation sheets, teacher and student response questionnaires, and a learning interest questionnaire. The results of the study indicate that interactive learning media are valid and practical for use in learning activities. In addition, the application of the media effectively increases students' interest in learning. Therefore, interactive learning media based on game-based learning and ethnomathematics using Lumi Education offers an alternative solution to improving students’ learning interest in mathematics, particularly on the topic of straight line equations.